Modeling different modes of failure in reinforced concrete beams combining tensile and shear-frictional damage models and bond–slip coupling for non-matching reinforcement and fragmented concrete meshes - Villa dos Santos, Andrei F. [UNESP]; Gimenes, Marcela [UNESP]; Rodrigues, Eduardo Alexandre [UNESP]; Cleto, Pedro R. [UNESP]; Manzoli, Osvaldo Luís [UNESP] (Elsevier, 2025)
A new strategy to predict the different failure processes of reinforced concrete members via macroscale modeling is proposed. In the mesh fragmentation framework, the technique relies on the use of condensed high aspect ratio interface elements and two independent damage models (tensile and shear-frictional), enabling specific energy dissipation for each fracture propagation mode, as well as modeling the formation and propagation of multiple fractures in the concrete. Additionally, to simulate reinforced concrete members, coupling finite elements are incorporated to model the interaction between the concrete and steel reinforcements, considering appropriate bond–slip behavior. Uniaxial compression tests are carried out to assess the ability of the strategy to predict the failure mechanism of concrete and to study the influence of material parameters such as cohesion and friction angle. The predictions of reinforced concrete beams with different spans, cross sections, and reinforcements are in good agreement with the experimental results reported in the literature, particularly with respect to the failure modes. The experimentally observed relationships between the geometric parameters and failure modes (flexural, shear and crushing failure modes) of reinforced concrete beams can also be properly predicted via the proposed approach.
Keywords: Condensed high aspect ratio interface element (HAR-IE); Coupling finite elements; Flexural; Mesh fragmentation technique (MFT); Reinforced concrete (RC) beams; Shear and crushing failure modes